Learning Strategies in Speaking Classroom: A Teaching Acceleration for Second Language - Nur Asiza Syarif; Farida bt, Abd. Rauf (Eduvelop: Journal of English Education and Development, 2022)
The objective of the research is to get information of learning strategies which are commonly used by the eighth grade Students of the SMP Negeri 2 in speaking in the classroom and to know the strategies which are most effective to improve the speaking skill according to the eighth grade Students of the SMP Negeri 2 Parepare. This study apply a descriptive method. To get the good result, this study applies two questionnaires about students’ learning strategies and which learning strategies are most affective the students’ learning. The population of this research is the third semester students of the eighth grade Students of the SMP Negeri 2 Parepare in academic year 2020/2021. The sample of this study was 35 students. The result of this study found that the students 1) using English in classroom, 2) asking by using English, 3) actively imitating their teacher, 4) translating difficult sentences, 5) making quiz acively, and 6) correcting the structure mistake making by their friends, 7) paying attention to vocabulary, tenses, pronunciation, etc.